Optimised CORDIC‐based atan2 computation for FPGA implementations. Issue 19 (1st September 2017) - Torres, V.; Valls, J.; Canet, M.J.
Abstract : A method for the implementation of the atan2 operator based on the coordinate rotation digital computer algorithm is described. In the proposal, the computation of the z ‐path takes advantage of the look‐up table‐based FPGA resources to reduce by between 17 and 25%, without performance deterioration, the overall area of the unrolled architecture.